The Antioxidant and Cytotoxic Effects of Cosmos caudatus Ethanolic Extract on Cervical Cancer - Betty Nurhayati; Ira Gustira Rahayu; Sonny Feisal Rinaldi; Wawan Sofwan Zaini; Ervi Afifah; Seila Arumwardana; Hanna Sari Widya Kusuma; Rizal Rizal; Wahyu Widowati (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Oxidative stress is closely related to all aspects of cancer. Cosmos caudatus ethanolic extract (CCEE) has been proved to have antioxidant effect that inhibited cancer cell growth due to its bioactive compounds such as catechin, quercetin and chlorogenic acid. This study aimed to evaluate antioxidant and anticancer activity of CCEE and its compounds.METHODS: Total phenol was measured according to the Folin-Ciocalteu method. Catechin, quercetin and chlorogenic acid contained in CCEE were identified by high-performance liquid chromatography (HPLC). Antioxidant activity was evaluated by 2,2′-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS)-reducing activity, 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging activity, and ferric reducing antioxidant power (FRAP) activity test. The cytotoxic activity of CCEE was determined by MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] assay on HeLa cells.RESULTS: The result showed that total phenol of CCEE was 181.64±0.93 µg Cathecin/mg extract. ABTSreducing activity test showed that catechin had the highest activity (2.90±0.04 µg/mL), while CCEE had moderate activity compared to other compounds. FRAP activity test demonstrated that catechin had the highest activity (315.83 µM Fe(II)/µg) compared to other compounds. DPPH scavenging activity of CCEE was 22.82±0.05 µg/mL. Cytotoxicity test on HeLa cell showed that CCEE had lower activity (inhibitory concentration (IC)50= 89.90±1.30 µg/mL) compared to quercetin (IC50 = 13.30±0.64 µg/ mL).CONCLUSION: CCEE has the lowest antioxidant activity compared to quercetin, catechin, and chlorogenic acid and has the lowest anticancer activity compared to quercetin. However, CCEE and its compounds has potential as antioxidant and anticancer properties.KEYWORDS: antioxidant, anticancer, catechin, Cosmos caudatus, quercetin